(3MeGSI CHj JeGes - (3CHh JeGe GdWGFj , CHh JeGe MHjH Hf ChS Hf GdMGQK GdWGFj,J (B231 (3g` s
(3ChdgG (B:s
(3HGH GdMeGSI bGd QLd ef HdYfHQ ef Hfj Jeje jbGd dg bQjW Hf Cfja ESdGej dh cfJ ef eGRf de JSJHM EHdj Hfh GddbjWI ef Pgd Hf TjHGfG s
(3BNQgG (B:s
(3dgG ae edJbi TO ajg fbQJgG cCf eTaQgG bO WQ ef ajd CfjGHgG CVYaJ aj MdbgG YOOG eXgQGJ LejYG HGdOhGFjd s
(3GdfSNI eQhjI Yf GdEeGe GdLhGdjbjs
(3fSNI KGdKIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B170s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B271 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B691s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs